2010
DOI: 10.1007/s11033-010-0508-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an AP2/ERF-RAV transcription factor BnaRAV-1-HY15 in Brassica napus L. HuYou15

Abstract: Transcriptional regulation is thought to be important for stress tolerance and response of transcription factors. RAV subfamily transcription factor contains an AP2- and B3-DNA binding domain, which belongs to the AP2/ERF family. It encodes transcriptional regulators with a variety of functions involved in the developmental and physiological processes in plants. Here, a RAV-like gene, BnaRAV-1-HY15, was isolated from Brassica napus L. cv HuYou15. Sequence homology analysis revealed that the BnaRAV-1-HY15 facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Two Arabidopsis RAV genes ( AtRAV1L and AtRAV2 ) are transcriptionally down-regulated by drought and salt stress (Fu et al, 2014). However, Brassica napus BnaRAV-1-HY15 expression is actually induced by NaCl and PEG treatments, even though it shares high identity with the AtRAV2 of Arabidopsis (Zhuang et al, 2011). These studies emphasize that the functions of RAV genes in different species appear to be divergent.…”
Section: Discussionmentioning
confidence: 99%
“…Two Arabidopsis RAV genes ( AtRAV1L and AtRAV2 ) are transcriptionally down-regulated by drought and salt stress (Fu et al, 2014). However, Brassica napus BnaRAV-1-HY15 expression is actually induced by NaCl and PEG treatments, even though it shares high identity with the AtRAV2 of Arabidopsis (Zhuang et al, 2011). These studies emphasize that the functions of RAV genes in different species appear to be divergent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the expression of GhERF2, GhERF3 and GhERF6 increased rapidly under drought, cold and salt stresses and also in the presence of ABA and ethylene in cotton (Jin et al 2010). In Brassica napus, BnaRAV-1-HY15 was induced by ABA (Zhuang et al 2011). Wheat transgenic plants overexpressing cotton GhDREB gene that has high homology with AtRAP2.1 were shown to provide enhanced tolerance to drought, salt and freezing stresses (Gao et al 2009).…”
Section: Cellular Communication and Signal Transduction Related Genesmentioning
confidence: 99%
“…RAV subfamily, related to ABI3/VP1 transcription factors, might be also involved in stress responses. B. napus RAV‐1‐HY15 is induced by cold, NaCl, and PEG treatments (Zhuang et al 2011). Overexpression of the CARAV1 gene in transgenic Arabidopsis plants induced some PR genes and enhanced resistance against infection by Pseudomonas syringae and osmotic stresses by high salinity and dehydration (Sohn et al 2006).…”
Section: Introductionmentioning
confidence: 99%